The Analysis of Sub-saharan African Surgical Sublications - Alımoglu, Orhan; Colapkulu, Nuray; Leblebici, Ihsan Metin (International Journal of Human and Health Sciences (IJHHS), 2019)
Objectıve: Medical education and health have been accelerated in Sub-Saharan Africa (SSA) over the years, however scientific contrubition of SSA is not adequate. The aim of this study is to document the studies published by scientists from SSA. Method: This study was conducted via searching the database of PubMed by using the words “Sub-Saharan Africa AND Surgery”, between 01.01.2016 and 31.12.2016. Results and dıscussıon: A total of 582 articles were found and reviewed. Irrelevant 305 (52%) articles were excluded. There were 277 (48%) surgical articles and 82 (30%) of the studies were conducted in the field of general surgery which were reviewed for this study. Fourty-two (51%) articles were published by local scientists from 15 SSA countries; 15 (18%) articles by the researhers outside of Africa and 25 (30%) articles were collaboration studies between African and western countries. Twenty (24%) articles were published in African based journals whereas 62 (76%) were published in international journals. The most common topics among articles were gastrointestinal system diseases, trauma and breast cancer, respectively.Conclusıons: In conclusion the number and subjects of publications held by local scientists is inadequate, and therefore, scientific researhers should be supported. International Journal of Human and Health Sciences Vol. 03 No. 02 April’19. Page: 101-104